STRATEGI PEMBELAJARAN KONTEKSTUAL MATERI PECAHAN PADA MATEMATIKA SISWA SD - Muhammad Syani; Mia Aji Rahmawati; Himatul Ulya; Dian Mustika Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics plays a fundamental role in primary education, yet many elementary school students face difficulties in understanding the abstract concept of fractions. This study aims to explore the integration of Contextual Teaching and Learning (CTL) as a strategy to enhance students' conceptual understanding of fractions. The research employs a qualitative approach with a literature review method, collecting and analyzing scientific articles, research reports, and academic books related to contextual learning in primary education. Data analysis was conducted using content analysis and descriptive qualitative techniques. The results indicate that the integration of contextual approaches significantly improves student participation, motivation, and learning outcomes in learning fractions. Specifically, three dominant effective strategies were identified: (1) the use of concrete and manipulative media (such as paper folding and fraction blocks), (2) contextual problem-based learning using real-life word problems, and (3) group collaboration through everyday scenarios. Grounded in constructivism, CTL bridges the gap between concrete sensory experiences and formal mathematical symbols. In conclusion, utilizing real-life situations and concrete models helps primary students reconstruct fraction concepts actively and meaningfully, making it highly recommended for mathematics educators.